Chapter Seasonal dynamics of cadmium and plumbum in the Turia and Pripyat rivers - Humeniuk, Halyna (Proceedings e report, 2020)
The anthropogenic pressure on aquatic ecosystems leads to a significant transformation of their quantitative and qualitative composition. Many rivers of Ukraine are polluted. The object of research was the surface waters of the rivers Pripyat and Turiya (Volyn region, Ukraine). Analysis of the qualitative and quantitative composition of toxicants (Cd, Pb) showed that the waters of the rivers have high level of pollution. A negative phenomenon in the studied reservoirs is a significant excess of concentrations of heavy metals: lead in 118 times and cadmium in 110 times in August.